Context and conditions matter: Stress and strain in the exercise of leadership power. (February 2020) - Krauter, Jörg
Current research shows that a significant number of leaders suffer from strain which effects their application of power. This is a highly relevant leadership issue in today's challenging business world. This study applies conservation of resources theory and the critical leadership studies approach to re-think leadership dynamics such as stressors and strain factors and their influence on power-related behaviour. The leader role, leader–member relations, workplace, organization and environment can be identified as resource passageways which create, maintain or limit the development of resources such as power-related behaviour. Research on the self-assessments of 43 German leaders from private sector shows that strain factors, leader role and leader–member relations can influence power-related behaviour. The data also show the importance of clarifying demands and expectations to prevent resource loss, otherwise overtaxed leaders are highly likely to use negative forms of power-related behaviour. The results demonstrate the need to improve understanding of the leader role with its increasing demands to be more flexible, agile and ambidextrous, but also to accept the human limitations of those who take on senior positions. Hence, the study findings demonstrate that context and conditions shape the situation in which leaders are embedded and therefore how to handle power is not only a problem for leaders themselves. The article also discusses the limitations of these findings and outlines possible directions for future research.